PERTUMBUHAN PEREPAT (Combretocarpus rotundatus Miq) PADA MACAM MEDIA DENGAN PENAMBAHAN PUPUK NPK DI PERSEMAIAN - Kasli Kasli; H. A. Oramahi; Gusti Hardiansyah (EnviroScienteae, 2021)
It is highly hoped that the recovery of damaged and degraded peat swamp forest will be implemented immediately, given the function of peat swamp forest which is very vital for the sustainability of the ecosystem. The development of tree species original in the perepat type of peat swamp forest (Combretocarpus rotundatus Miq) is needed. Provision of good and quality fasting type seeds can be done by seeding in the nursery. This study aims to find the best type of planting medium in increasing accelerator growth in the nursery and obtaining the right dosage of NPK fertilizer to increase the growth of the nursery accelerator. The media used were peat soil and ultisol soil with the following treatment design : (M1 = peat soil, M2 = ultisol soil, and M3 = mixture of peat soil and ultisol soil with a ratio of 1: 1), then the addition of the NPK fertilizer dosage used is (P0 = 0 g, P1 = 75 mg, P2 = 150 mg , P3 = 225 mg, and P4 = 300 mg.). using the factorial experiment method with a completely randomized design. The results showed that the most suitable medium for the growth of seedlings was using peat media. The application of NPK fertilizer can increase the growth of fasting perepat in the nursery until the age of 3 months by giving a significant effect on growth in height, diameter and number of leaves. The dose of NPK fertilizer is 225 mg. resulting in the best and economic growth enhancement.